(untitled) (Islamic Sciences Journal, 2023)
ABSTRACT The research aims to highlight the explanatory efforts of the scholar Shabeer Ahmed Al-Othmani in his book: Fateh Al-Mulhim with the explanation of Sahih Muslim. Despite the fact that the book is specialized in the science of hadith, the Mark Shabeer had explanatory pauses in a brief and clear phrase, and from here came this research marked with (interpretive efforts of the sign Shabeer Ahmed Al-Othmani in his book Fateh Al-Mulhim with the explanation of Sahih Muslim for his interpretation of some Meccan verses - from Surat Al-An’am and Al-A’raf as a model).